Simultaneous Catalytic Removal of NOx and Diesel Soot Particulates Over LaSrBO4 (B = Mn, Cu, Co, Fe) Oxides - Ma, Z.; Zhu, Y.F.; Ding, T.; Qin, Y.N.; Li, Z.J. (Asian Journal of Chemistry, 2012)
A series of LaSrBO4 complex oxides were prepared by the citric acid complexion and characterized by XRD, XPS, H2-TPR, NO-TPD and catalytic activity experiments. According to the investigations, LaSrMnO4 shows the best performance, the maximum conversion rate from NO to N2 is up to 69 %. The existence of oxygen is very important for the simultaneous removal of NOx and diesel soot particulates. The low temperature desorbed NO species would mainly influence the N2 yield. The mobility of adsorbed oxygen species would mainly influence the selectivity of the reaction.